A Hidrelétrica Belo Monte: da controvérsia sobre energia limpa à produção da "verdade científica"1 - Camila Dellagnese Prates; Léo Peixoto Rodrigues (Ciências Sociais Unisinos)
The article, linked to the social studies ofscience and, more specifically to scientific con-troversies, problematizes the energy issue from hydroelectric plants as a source of "clean energy"generation. Thus, the controversy ofclean energygeneration is presented in detail in plants of a subtropical climate (Northern Brazil), taking as an empirical investigation the Brazilian Plant called Hydroelectric Belo Monte, located in Pará. The methodology used to describe the controversy was the cartography of the controversy (Latour, 2016). In the end, it is demonstrated that the "reality" is fabricated by technoscientific studies that direct the analysis of the studies excluding important variables of their equations generating environmental conflicts related to the controversy of the clean energy.